285 Markov model simulation of paediatric abusive head trauma primary prevention and screening programs. (1st September 2016) - Bailhache, Marion; Bénard, Antoine; Salmi, Louis-Rachid
Abstract : Background: Paediatric Abusive Head Trauma (PAHT) is an important cause of morbidity and child-abuse deaths. Several prevention programs exist but their impact is difficult to estimate by lack of knowledge about the beginning of PAHT, difficulties to identify all cases, and the need for large cohorts. We modelled the potential impact of primary prevention and screening programs of PAHT in a hypothetical cohort of 800, 000 newborns. Methods: We developed Markov models without intervention, and with primary prevention based on current interventions, screening during repeated consultations, addressed to all families until children are two-years old, and with both programs. Several scenarios were tested regarding potential side effects for parents being mislabeled as abusers (assumed or not to increase the risk of PAHT and decrease participation in screening) and length of the preclinical phase. The time horizon was two years with cycles of fifteen days. Outcomes were number of deaths and abused children avoided. Uncertainty was specified with probability distributions based on literature, or extreme possible values in absence of data. Results: After two years, the median number of death avoided through primary prevention would vary from 6 (CI: 95%: 2–11) to 28 (6–51) for 100 000 newborns, depending on the probability of PAHT and scenario. Screening could prevent up to 6 (0–29) deaths or cause up to 66 (0–361) deaths for 100, 000 children born alive. The impact of both programs on mortality and morbidity was uncertain. Conclusions: Our model confirmed the potential benefits of primary prevention and documented the huge uncertainty regarding benefits associated with screening of PAHT. Better estimating the effects of wrongly identifying caregivers as abusers, the evolution of PAHT, and the performance of tests to earlier identify child-abuse are necessary.